Pride Parades and/or Prayer Processions: Contested Public Space in Serbia #Belgrade Pride 2014 - Igrutinović, Danica (Journal of empirical theology, 2015)
In post-Yugoslav countries, national identity seems to be increasingly defined by the formulation of a traditional discourse on sexuality and gender, culminating in a growing interference of religious institutions with national debates and policies on lgbt-rights. In this paper we aim to gain more insight into the discursive effects of such sexual nationalist discourse by exploring responses of the Serbian Orthodox Church to the 2014 Belgrade Pride parade. Drawing from theories on religious and sexual nationalism and queer geography, we will argue that while the Serbian Orthodox discourse on homosexuality is becoming more secular, this secularization of public speech is compensated by a strategy of reclaiming the streets of Belgrade through politically charged public religious ritual. As the church is in this way making its anti-lgbt attitude physical and visible, Serbian citizens are increasingly requested to agree to Church teachings on sexuality and gender as a prerequisite for religious participation, resulting in an increasing divide between those “within” and “without” the community of Orthodox Serbs.